Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung Yang Menginap Pada Hotel Mesra Di Kota Samarinda - Permatawati P, Grace (Jurnal Syntax Fusion, 2022)
Samarinda City is an area that has considerable business competition in the field of hotel accommodation. Hotel Mesra Samarinda as a company engaged in hospitality services experiences fluctuating levels of visits. One way to increase hotel guest satisfaction is to improve the quality of service by looking at the needs and desires for service as a key factor for the success of the hotel. The type of research used is descriptive research, namely research conducted by describing or explaining the variables studied and to come to a conclusion. The data analysis used is the classical assumption test which is a prerequisite test for further data analysis and hypothesis testing for decision making based on data analysis. The results showed that 66 respondents (66)% were female respondents, 73% aged 21-30 years were 73%, 54 respondents were undergraduate or 54%, 60 (60)% were from outside Samarinda City. Reliability, responsiveness, assurance, empathy and physical evidence variables have a significant and partial effect on visitor satisfaction. the most influential variable is the physical evidence variable.Quality of service